Discovery of four new species of the genus Planaeschna from Southwestern China (Odonata: Anisoptera: Aeshnidae) - Zhang, Hao-Miao; Cai, Qing-Hua (Zootaxa, 2013)
Four new species of the genus Planaeschna, P. robusta sp. nov. (holotype male; Mt. Emeishan, Emeishan City, Sichuan Province, China, 16. VIII. 2007), P. maculifrons sp. nov. (holotype male; Mt. Emeishan, Emeishan City, Sichuan Province, China, 20. VIII. 2007), P. caudispina sp. nov. (holotype male; Mt. Qingchengshan, Dujiangyan City, Sichuan Province, China, 30. VIII. 2007) and P. monticola sp. nov. (holotype male; Sanjiacun Stream, Fengyi Town, Dali City, Yunnan Province, China, 19. XI. 2012) are described and illustrated and diagnosed from their congeners. All the holotypes have been deposited in the Collection of Aquatic Animals, Institute of Hydrobiology, Chinese Academy of Sciences, Wuhan City, Hubei Province, China. Brief notes on the biology of each species are also provided.